Blink Patterns: Reading from a Computer Screen versus Hard Copy - Chu, Christina A.; Rosenfield, Mark; Portello, Joan K. (Optometry and vision science, 2014)
PURPOSEMany subjects experience ocular and visual symptoms during computer use. Previous studies have reported a reduced blink rate during computer operation and suggested that this may account for some of the symptoms, particularly dry eye. However, these earlier investigations failed to include an appropriate control condition. To determine whether it is computer screen viewing that produces the change in blink rate, the present study compared blink patterns when reading from either a desktop computer monitor or a hard copy printed text under equivalent viewing conditions. METHODSSubjects (N = 25) were required to perform a continuous 20-minute reading task from either a desktop computer screen or a printed hard copy page at a viewing distance of 50 cm. Identical text was used in the two sessions, which was matched for size and contrast. Target viewing angle and luminance were similar for the two conditions. Subjects were videotaped during the task to determine their blink rate and amplitude. Immediately after the task, subjects completed a questionnaire regarding ocular symptoms experienced during the trial. RESULTSMean blink rates for the computer and hard copy conditions were 14.9 and 13.6 blinks per minute, respectively (p = 0.58). However, a significantly higher percentage of incomplete blinks was observed for the computer condition (7.02 vs. 4.33%; p = 0.02). No significant correlation was found between the symptom score and the percentage of incomplete blinks. CONCLUSIONSWhen compared with an equivalent hard copy control condition, blink rates were not reduced during computer operation. It is proposed that the previously observed differences in blink rate are more likely to be produced by changes in cognitive demand rather than the method of presentation. However, a higher percentage of incomplete blinks was noted during computer operation, which may have been associated with visual fatigue.